Answer:
Additive inverse is
![g(x)=6x^(2)-x+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6jyza4pm1c137oy2x4nv7prffigvagmrw2.png)
Explanation:
We have the function
.
Now, for the additive inverse, we have the property that, there exists a function g(x) such that f(x)+g(x) = g(x)+f(x) = 0.
So, we have,
f(x)+g(x) = g(x)+f(x) = 0
i.e.
![(-6x^(2)+x-2)+g(x)=g(x)+(-6x^(2)+x-2)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rvxcmdj6shrdwecx2hyc45thm1zlo5q9ih.png)
i.e.
and
![g(x)+(-6x^(2)+x-2)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4xbmkn9d2mlvpneou7r2hbuuzqs31jhhm5.png)
i.e.
and
![g(x)=6x^(2)-x+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6jyza4pm1c137oy2x4nv7prffigvagmrw2.png)
i.e.
![g(x)=6x^(2)-x+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6jyza4pm1c137oy2x4nv7prffigvagmrw2.png)
Thus, the additive inverse of
is
.